Pengembangan Budaya Sekolah di SMP PGRI 11 Palembang dan SMP IT Bina Insan Islamic School Rambutan - Chan, Rahul; Oskar, Ruani; Ali, Marwan; Febrianto, Andre; Fauzi, Muhammad; Sukardi, Ismail (Jurnal Ilmiah Global Education, 2025)
School culture serves as a fundamental foundation in shaping a positive, conducive, and character-oriented learning environment. This study aims to describe and analyze the strategies and practices involved in developing school culture at SMP PGRI 11 Palembang and SMP IT Bina Insan Islamic School Rambutan. Using a qualitative approach, the research explores the values, traditions, and practices that form an integral part of the cultural development in both schools. The findings reveal that the development of school culture is strongly influenced by the institution's vision and mission, as well as the active involvement of all school components, including students, teachers, and parents. A positive school culture has been shown to enhance students’ learning motivation and academic achievement. The results of this study are expected to serve as a reference for other educational institutions in cultivating an effective and sustainable school culture.